Hospital Readmission Within 2 Years Following Adult Thoracolumbar Spinal Deformity Surgery: Prevalence, Predictors, and Effect on Patient-derived Outcome Measures. Issue 17 (September 2016) - Passias, Peter G.; Klineberg, Eric O.; Jalai, Cyrus M.; Worley, Nancy; Poorman, Gregory W.; Line, Breton; Oh, Cheongeun; Burton, Douglas C.; Kim, Han Jo; Sciubba, Daniel M.; Hamilton, D. Kojo; Ames, Christopher P.; et al.
Abstract : Study Design: A retrospective review of prospective multicenter database. Objective: The aim of this study was to identify factors influencing readmission, reoperation, and the impact on health-related quality of life outcomes (HRQoLs) in adult spinal deformity (ASD) surgery. Summary of Background Data: Many ASD patients experience complications requiring readmission. It is important to identify baseline/operative factors leading to rehospitalizations and reoperation, which may impact outcomes. Methods: Inclusion criteria: ASD surgical patients (age >18 yrs, major coronal Cobb ≥20°, sagittal vertical axis ≥5 cm, pelvic tilt ≥25°, and/or thoracic kyphosis >60°) with complete baseline, 1-, and 2-year follow-up. Patients were grouped on the basis of readmission occurrence (yes/no) and type [medical (no reoperation) vs . surgical (revision surgery)]. Readmissions caused by infections requiring surgical treatment ( e.g., deep infections) were considered reoperations. Univariate and multivariate analyses determined readmission and reoperation predictors. Repeated measures mixed models evaluated readmission impact on HRQoLs at 1 and 2 years. Results: Three hundred thirty-four patients were included: 76 (22.8%) readmissions, involving 65 (85.5% of 76) reoperations (surgical readmission) and 11 (14.5% of 76) medical readmissions. The most common surgical readmission indication ( n = 65) was implant complications (36.9%; rod breakage n = 13); the most common medical readmission indication was infection (36.4%, n = 4), treated with antibiotics. Noninfectious medical readmission ( n = 7) included pleural effusion, deep vein thrombosis (DVT), intraoperative blood loss, neurologic, and unspecified. Readmission predictors: increased number of major peri-operative complications [odds ratio (OR) 5.13, P = 0.014], infection presence (OR 25.02, P = 0.001), implant complications (OR 6.12, P < 0.001), and radiographic complications (DJK, proximal junctional kyphosis, pseudoarthrosis, sagittal/coronal imbalance) (OR 16.94, P < 0.001). HRQoL analysis revealed overall improvement of the full cohort ( P < 0.01), though the 76 readmitted improved less overall and at each time point P < 0.001) except in 6-week MCS ( P = 0.14). Conclusion: Major peri-operative, implant, radiographic, and infection complications during index were associated with increased readmission odds. Implant complications most frequently caused surgical readmissions. Readmitted patients improved in outcome scores, although less compared with the nonreadmitted cohort, yet displayed reduced 6-week SF-36 Mental Component Summary. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text